Teacher Empowerment through E-Comics to Improve Mathematical Connections in the Harapan Bunda Semarang Learning Community: Teacher Empowerment through E-Comics - Basir, Mochamad Abdul; aminudin, mohamad; suyitno, amin; khasanah, uswatun; salma, emilia (JURNAL ABDIMAS SERAWAI, 2025)
The limited variety of learning media and digital assessments is one of the challenges for teachers in improving students' mathematical connections. To overcome this, this community service activity aims to empower junior high school mathematics teachers in the Harapan Bunda Semarang Learning Community in designing e-comics and interactive digital assessments to improve students' mathematical connection skills. The target partners consist of 20 mathematics teachers who are active in the Harapan Bunda Semarang Learning Community. This program is implemented for two months with a participatory training approach consisting of three stages: (1) socialization and mapping of teacher needs, which aims to understand the level of ability and needs of teachers related to digital learning media, (2) training in creating e-comics based on contextual problems that are relevant to junior high school mathematics material, as well as designing digital assessments using the Liveworksheets platform, and (3) direct practical assistance by a team of lecturers and students from the Mathematics Education Study Program, FKIP, Sultan Agung Islamic University. The results of the activity showed an average increase in teacher competency scores of 60% in the posttest compared to the pretest, the quality of the e-comic products produced reached 86% based on the assessment rubric, and an average teacher satisfaction score of 4.7 out of 5. This increase reflects the positive impact of the training in significantly improving teachers' digital skills, while also contributing to efforts to develop more innovative and effective mathematics learning in schools